Convention on the Civil Aspects of International Child Abduction Article 13/1(b) and “Domestic Violence”: A Critical Review - Onur Can Saatcıoğlu (Public and Private International Law Bulletin)
The Convention of 25 October 1980 on the Civil Aspects of International Child Abduction aims to secure the prompt return of children who were wrongfully removed to, or retained in, a Contracting State, in violation of the rights of custody or access under the law of another. The Convention is based on the assumption that the best interests of the child is best preserved in the state of the habitual residence of the child concerned. That being said, the Convention also allows for numerous exceptions to that assumption, again laid down in different provisions. Among these, the most frequently invoked exception is stipulated under article 13, paragraph 1-b. Often called the “grave risk exception”, this provision instructs the courts of the requested State that they are not bound to order the return of the child, as long as the person who opposes the return establishes that there is a grave risk that this would expose the child to physical or psychological harm or otherwise place him/her in an intolerable situation. One major problem with the above wording can be seen in cases where the abductor is a victim of domestic violence. The current framework of the Convention frequently leads to undesirable consequences, as it often fails to provide necessary protection both to the victim and the child. This paper is an effort to make this problem more visible. In the light of various criticisms made about this subject over time, the reasons behind it and the possible solutions to it will be examined.